Kudzu haylage characteristics, nutrient composition, and digestibility with different additives for ruminant feed - Kumalasari, Nur Rochmah; Permana, Asep Tata; Ridla, Muhamad; Ayuningsih, Novi; Noviyanti, Desy; Sunardi, Sunardi; Nurdianti, Risma Rizkia (Livestock and Animal Research, 2024)
Objective: This study aimed to evaluate the physical characteristics, nutrient composition and digestibility of Kudzu haylage that was treated with additives of rice bran, pollard, palm kernel and molasses.Methods: The study was performed into a completely randomized design with 5 treatments and 5 replications. The treatments were control: Kudzu haylage without additive (P0), Kudzu haylage and 5% rice bran (P1); Kudzu haylage and 5% pollard; Kudzu haylage and 5% palm kernel; Kudzu haylage and 5% molasses. The data were analyzed by Analysis of Variance, mean comparisons by the Tukey test were performed using R x64 4.1.0.Results: The results showed that in the haylage making process, all additives improve Kudzu haylage physical characteristics, nutrient composition, and digestibility. Kudzu haylage with molasses addition resulted brownish yellow color, soft crumble texture, sour smell with 2.4% spoilage on haylage surface. The Fleigh value, nutrient composition and digestibility were increased with molasses addition.Conclusions: Based on the physical characteristic, nutrient composition and digestibility of Kudzu could be preserved as haylage with additives of rice bran, pollard, palm kernel and molasses. The best treatment on Kudzu haylage was 5% molasses addition that improved physical characteristics, nutrient composition, and digestibility.